Revised STandards for Reporting Interventions in Clinical Trials of Acupuncture (STRICTA): Extending the CONSORT Statement - Hugh MacPherson; Douglas G. Altman; Richard Hammerschlag; Youping Li; WU Tai-xiang; Adrian White; David Moher (2010)
The STandards for Reporting Interventions in Clinical Trials of Acupuncture (STRICTA) were published in five journals in 2001 and 2002. These guidelines, in the form of a checklist and explanations for use by authors and journal editors, were designed to improve reporting of acupuncture trials, particularly the interventions, thereby facilitating their interpretation and replication. Subsequent reviews of the application and impact of STRICTA have highlighted the value of STRICTA as well as scope for improvements and revision. To manage the revision process a collaboration between the STRICTA Group, the CONSORT Group, and the Chinese Cochrane Centre was developed in 2008. An expert panel with 47 participants was convened that provided electronic feedback on a revised draft of the checklist. At a subsequent face-to-face meeting in Freiburg, a group of 21 participants further revised the STRICTA checklist and planned dissemination. The new STRICTA checklist, which is an official extension of CONSORT, includes six items and 17 sub-items. These set out reporting guidelines for the acupuncture rationale, the details of needling, the treatment regimen, other components of treatment, the practitioner background, and the control or comparator interventions. In addition, and as part of this revision process, the explanations for each item have been elaborated, and examples of good reporting for each item are provided. In addition, the word "controlled" in STRICTA is replaced by "clinical," to indicate that STRICTA is applicable to a broad range of clinical evaluation designs, including uncontrolled outcome studies and case reports. It is intended that the revised STRICTA, in conjunction with both the main CONSORT Statement and extension for nonpharmacologic treatment, will raise the quality of reporting of clinical trials of acupuncture.